Application of Stem Cells Shows Antiinflammatory Effect in an Irradiated Random Pattern Flap Model - Müller-Seubert, Wibke; Fuchs, Lena; Horch, Raymund E.; Distel, Luitpold; Frey, Benjamin; Renno, Isabell; Erber, Ramona; Arkudas, Andreas (Journal of Personalized Medicine, 2024)
Background: In reconstructive surgery, local flaps might develop tissue necrosis or partial flap loss especially after previous irradiation, which may be necessary in many tumor entities. The application of stem cells seems promising to improve flap perfusion and might be a possible solution to optimize flap survival. Methods: Twenty rats received harvesting of bilateral random pattern fasciocutaneous flaps. The right flaps received 20 Gy ionizing radiation 4 weeks prior to the surgery, while the left flaps served as the non-irradiated control. After flap harvest, four different stem cell mixtures (5 × 106 ASC, ASC-HUVEC, MSC, MSC-HUVEC) were applied under both right and left flaps using 1 mL fibrin glue as the delivery vehicle. Flap size and its necrotic area were examined clinically. Two weeks after the surgery, HE staining and immunohistochemical staining for CD68 and ERG, as well as PCR analysis (Interleukin 6, HIF-1α and VEGF), were performed. Results: Application of ASCs, ASCs-HUVECs and MSCs resulted in a lower number of CD68-stained cells compared to the no cell group. The expression of Hif1α was higher in the ASC group compared to those in the MSC and previously treated no cell groups. Treatment with MSCs and MSCs-HUVECs prevented shrinking of the flaps in this series. Conclusion: Application of ASCs, MSCs and ASCs-HUVECs was shown to have an antiinflammatory effect. Treatment with MSCs and MSCs-HUVECs can prevent early shrinking of the flaps.
CRIS-Team Scopus Importer:2024-07-05
Keywords: ASC; HUVEC; irradiation; MSC; random pattern flaps